2015
DOI: 10.1016/j.gene.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Absence of germline mutations in BAP1 in sporadic cases of malignant mesothelioma

Abstract: Malignant mesothelioma (MM) is a uniformly fatal tumour caused predominantly by exposure to asbestos. It is not known why some exposed individuals get mesothelioma and others do not. There is some epidemiological evidence of host susceptibility. BAP1 gene somatic mutations and allelic loss are common in mesothelioma and recently a BAP1 cancer syndrome was described in which affected individuals and families had an increased risk of cancer of multiple types, including MM. To determine if BAP1 mutations could un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 93%
See 4 more Smart Citations
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 93%
“…Investigators have examined BAP1 in families: i) with high incidence of MM [3,7,9,11,14]; ii) referred to genetic or cancer centers for uveal melanoma [9,12,15] or other melanocytic tumors [13,17]; iii) affected by basal cell carcinoma [16]; iv) having a family history suggestive of the BAP1 cancer syndrome [18]. Other families were examined as part of asbestos surveillance program [10].…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 99%
See 3 more Smart Citations